TEMPOROMANDIBULAR JOINT SYNOVIAL CHONDROMATOSIS: A RARE CASE - Doğan Durna; Binali Çakur; Neslihan Bayındır (Cumhuriyet University, 2021)
Synovial chondromatosis (osteochondromatosis) is a rare lesion originating from the synovial membrane. It develops as a result of metaplasia of the tendon sheath or synovial membrane of the bursa in the joint and causes the formation of chondral or osteochondral foci in the synovium. These cartilaginous lesions can cause secondary degenerative changes as free bodies within the joint. Between the ages of 30 and 50, the knee joint is less commonly seen in the hip, ankle, shoulder and elbow joints. Clinically, joint pain and progressive limitation of motion, effusion and recurrent locking in some cases are seen. In this case, we aimed to present SC radiologic (CBCT and MR) and clinical findings in TME of a 53 years old female patient who applied to our clinic for synovial chondromatosis.